2018
DOI: 10.1038/s41598-018-31035-y
|View full text |Cite
|
Sign up to set email alerts
|

Regional variations in stiffness in live mouse brain tissue determined by depth-controlled indentation mapping

Abstract: The mechanical properties of brain tissue play a pivotal role in neurodevelopment and neurological disorders. Yet, at present, there is no consensus on how the different structural parts of the tissue contribute to its stiffness variations. Here, we have gathered depth-controlled indentation viscoelasticity maps of the hippocampus of acute horizontal live mouse brain slices. Our results confirm the highly viscoelestic nature of brain tissue. We further show that the mechanical properties are non-uniform and at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
95
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 85 publications
(101 citation statements)
references
References 69 publications
6
95
0
Order By: Relevance
“…Other studies investigated the contribution of myelin in WM fibers as a mechanical support structure in the brain, suggesting a higher stiffness of WM than GM . In addition, recent dynamic indentation experiments in hippocampal tissues showed that stiffness appears to be lower in areas where cell nuclei density is high . These examples illustrate that regional values of brain stiffness, including WM‐GM ratios, provide rich structural information, which still remain to be disentangled.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Other studies investigated the contribution of myelin in WM fibers as a mechanical support structure in the brain, suggesting a higher stiffness of WM than GM . In addition, recent dynamic indentation experiments in hippocampal tissues showed that stiffness appears to be lower in areas where cell nuclei density is high . These examples illustrate that regional values of brain stiffness, including WM‐GM ratios, provide rich structural information, which still remain to be disentangled.…”
Section: Discussionmentioning
confidence: 92%
“…43 In addition, recent dynamic indentation experiments in hippocampal tissues showed that stiffness appears to be lower in areas where cell nuclei density is high. 44 These examples illustrate that regional values of brain stiffness, including WM-GM ratios, provide rich structural information, which still remain to be disentangled. Different dynamic ranges of test methods, prestrains, geometric conditions, and in vivo versus ex vivo conditions including blood perfusion effects translate into different mechanical measures that are hard to compare among different modalities.…”
Section: F I G U R Ementioning
confidence: 99%
“…6A. Specifically, all regions stiffen with strain, revealing the non-linear viscoelastic properties of fixed chicken embryos, a result that highlights the importance of measuring the mechanical properties of embryonic tissues in depth-controlled mode (Antonovaite et al, 2018).…”
Section: Resultsmentioning
confidence: 87%
“…The indenter is based on ferrule-top technology (Chavan et al, 2010;Gruca et al, 2010), where the deflection of a micro-machined cantilever, equipped with a spherical tip, is used to determine the viscoelastic properties of the embryo via depth-controlled oscillatory ramp indentation ( Fig. 1A-D) (Antonovaite et al, 2018;van Hoorn et al, 2016). The OCT system images the embryonic structures during the indentation measurements and allows localizing the indentation point and evaluating the quality and the immobilization of the sample.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation